Effects of heterogeneous catalysis in porous media on nanofluid-based reactions. (January 2020) - Liu, Chunyan; Pan, Mingyang; Zheng, Liancun; Lin, Ping
Abstract: This paper studies a new type of homogeneous(HOM)-heterogeneous(HET) reactions in Al2 O3 -water-based nanofluid flowing through porous media over a stretching plate. Prior investigators have focused mainly on the catalytic effects on the plate, we model the influence of heterogeneous catalysis in porous media on these reactions. The HET reactions on the surfaces of porous media and plate are both governed by the first-order kinetics, while the HOM reaction in the fluid is given by the isothermal cubic autocatalytic kinetics. In addition, the thermal conductivity of four distinct shapes of nanoparticle, sphere, brick, cylinder, and platelet, is taken into consideration with the Hamilton-Crosser model. The obtained nonlinear differential systems simplified by using similarity transformations are numerically calculated by the bvp4c algorithm. Results demonstrate that the increase of interfacial area of porous media enhances the rate of surface-catalyzed reaction and therefore porous media can greatly shorten the chemical reaction time. Moreover, we find that platelet nanoparticles exhibit the highest convective heat transfer capacity.